Elderly trauma patients and the effect of trauma scores on hospitalization decision - Gurgoze, Ramazan; Ozucelik, Dogac Niyazi; Yilmaz, Mustafa; Dogan, Halil (Turkish Surgical Assoc, 2022)
Objective: Hospitalization, mortality and trauma scores are important in trauma patients aged >= 65 years. The present study aimed to investigate the use of trauma scores in the prediction of hospitalisation and mortality in trauma patients aged >= 65 years. Material and Methods: Patients aged >= 65 years who presented to the emergency department with trauma over a one-year period were included in the study. Baseline data of the patients together with their Glasgow Coma Scale (GCS), Revised Trauma Score (RTS), Injury Severity Score (ISS), hospitalisation and mortality were analysed. Results: A total of 2264 patients were included in the study, of whom 1434 (63.3%) were women. The most common mechanism of trauma was simple falls. Mean GCS scores, RTSs and ISSs of the inpatients were 14.87 +/- 0.99, 6.97 +/- 0.343 and 7.22 +/- 5.826, respectively. Furthermore, a significant negative correlation was found between the duration of hospitalisation and GCS scores (r= -0.158, p< 0.001) and RTSs (r= -0.133, p< 0.001), whereas a positive significant correlation with ISSs (r= 0.306, p< 0.001) was observed. The ISSs (p< 0.001) of the deceased individuals were significantly elevated, whereas their GCS scores (p< 0.001) and RTSs (p< 0.001) were significantly decreased. Conclusion: All trauma scoring systems can be used to predict hospitalisation, but the results of the present study suggest that the use of ISS and GCS in making the decision regarding mortality is more appropriate.
Yaşlı travmalı hastalar ve travma skorlarının yatış kararına etkisi
Keywords: Emergencies; geriatrics; trauma; trauma scores